2019
DOI: 10.3390/ijerph16132403
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Community-Based Food Education Program on Nutrition-Related Knowledge in Middle-Aged and Older Patients with Type 2 Diabetes: Results of a Pilot Randomized Controlled Trial

Abstract: The purpose of this study was to evaluate the impact of a community-based food education program on nutrition-related knowledge in middle-aged and older patients with type 2 diabetes (T2D). Participants (n = 36; 65.9 ± 6.0 years old) were recruited in primary health care to a 9-month community-based lifestyle intervention program for patients with T2D and randomly assigned to an exercise program (control group; n = 16) or an exercise program plus a food education program (experimental group; n = 20). Nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Nutrition educators used face-to-face education that allowed T2DM patients to ask questions and discuss concerns. Unfortunately, food education programs report lower attendance compared with other educational interventions in T2DM patients [ 18 ]. Diabetes care in The Netherlands is currently focused on regular face-to-face consultations for self-management activities such as medical management (DM medicine and dietary advice), behavior and emotional management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nutrition educators used face-to-face education that allowed T2DM patients to ask questions and discuss concerns. Unfortunately, food education programs report lower attendance compared with other educational interventions in T2DM patients [ 18 ]. Diabetes care in The Netherlands is currently focused on regular face-to-face consultations for self-management activities such as medical management (DM medicine and dietary advice), behavior and emotional management.…”
Section: Discussionmentioning
confidence: 99%
“…Higher attendance of individual nutrition education may impact by T2DM prevalence by increasing knowledge levels. As common education methods, face-to-face nutrition education allowed patients with T2DM and nutritionists to ask questions and discuss issues [ 18 ]. To improve glycemic control, patients with T2DM should have good DM knowledge and follow a DM diet and nutritionists should prepare and deliver active and effective dietary education classes [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These systemic alterations may affect mental and physical functioning, increasing the chances of morbidity, multimorbidity, and mortality [ 30 ]. Older patients with diabetes may have macrovascular and microvascular complications and geriatric syndromes [ 28 , 31 ], so their control of diabetes is usually worse than younger patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Greece have revealed suboptimal nutrition knowledge among patients with DM [24][25][26], highlighting the need for an integrated approach to patient education. In parallel, randomized controlled trials (RCTs) have unanimously revealed improvements in glycemic control and disease prognosis following the implementation of nutrition education sessions [27,28]. In a study conducted in the USA [29] (Table 4), patients with T1DM and T2DM were educated on nutritional issues by an RDN and set individual goals based on the ADA/Morrison Health Care (MHC) recommendations.…”
Section: Discussionmentioning
confidence: 99%